Age- and Gender-Specific Reference Values for Physical Performance in Tunisian Youth Basketball Players - Chirine Aouichaoui; Mohamed Tounsi; Ghazi Racil; Oussama Tabka; Monia Zaouali; Nicola Luigi Bragazzi; Yassine Trabelsi (MDPI AG, 2024)
Background/Objectives: Physical performance is becoming increasingly critical in basketball, as it directly influences players' agility, power, and endurance. This study aimed to assess the progression of body composition and physical performance metrics across different ages and genders, establishing age- and gender-specific reference values for Tunisian basketball athletes. Methods: A total of 469 Tunisian basketball players (239 boys and 230 girls) were assessed and grouped by age. Anthropometric measures-including standing and sitting height, body mass, leg length, body mass index, fat mass, fat-free mass, body fat percentage, wingspan, and leg muscle volume-were collected alongside physical performance metrics. Performance tests included countermovement and squat jumps, change-of-direction speed, maximal oxygen uptake, flexibility, the five-jump test, and 5 m, 10 m, and 20 m sprints with and without the ball. Normative data were generated based on age and gender categories. Results: The findings revealed significant age-related improvements in both anthropometric and performance parameters. Boys consistently outperformed girls in physical and fitness-related measures, with gender differences becoming more pronounced with age. Stepwise regression analyses indicated that, for boys, body fat percentage, leg muscle volume, standing height, and wingspan were the best predictors of physical performance. For girls, body fat percentage, standing height, and sitting height were identified as key predictors. Conclusions: The newly established Tunisian reference values for physical performance in youth basketball provide valuable benchmarks that can support the development of explosive power and strength in players, aiding in talent identification and potentially enhancing individual and team performance outcomes.